EFFECT OF SILICON- POTASSIUM FOLIAR APPLICATION ON CONTENT OF NUTRIENTS AND THE DETOX-EFFECT IN URBAN GREEN AREAS - Гололобова, О. О.; Телегіна, Н. Є.; Толстякова, В. В. (Man and Environment. Issues of Neoecology)
It is shown that two-times application of silicon- potassium concentrate on leaves can optimise not only potassium but also nitrogen and phosphate components of plants. The effectiveness of the detox-effect of silicon- potassium fertilization for leaves is studied. The Pb concentration has decreased in the chestnut leaves in 14 times, Cd concentration – in 2 times. Cd concentration in the linden leaves has decreased in 2 times, Pb concentration – in 1.9 times. In the linden flowers the Cd concentration has decreased in 2.5 times.